Ordinary Fragmentation: Network Secession of Urban Centers in Jakarta - Wahyu Kusuma Astuti; Suryono Herlambang (The Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Drawing from the literature on ‘premium networked spaces’, introduced in Graham and Marvin’s seminal work Splintering Urbanism in 2001, this paper argues that splintering or fragmentation of networks – and ultimately urban space – is constituted in so-called premium enclaves in Jakarta. Our study exemplifies that significant land acquisition and discretionary zoning policy contribute to the splintering of Jakarta’s urban space. This paper uses the TB Simatupang corridor in South Jakarta and Puri Indah CBD in West Jakarta to illustrate the interplay between urban planning and secessionary space production in high-profile economic districts. Lastly, this paper proposes the ‘ordinary fragmented network’ as the norm and expands the idea of the splintering of marginalized parts of the city to also incorporate areas within premium network spaces as part of splintering urbanism. Abstrak. Diambil dari literatur tentang 'ruang jaringan premium' yang diperkenalkan dalam karya mani Graham dan Marvin pada tahun 2001, Splintering Urbanism, makalah ini berpendapat bahwa splintering atau fragmentasi jaringan – dan akhirnya ruang perkotaan, dibentuk dalam apa yang disebut kantong-kantong premium di Jakarta. Studi kami menunjukkan bahwa pembebasan lahan dan kebijakan zonasi diskresioner yang signifikan berkontribusi pada pecahnya ruang kota Jakarta. Makalah ini menggunakan koridor TB Simatupang di Jakarta Selatan dan CBD Puri Indah di Jakarta Barat untuk menggambarkan interaksi antara perencanaan kota dan produksi jaringan pemisahan di distrik ekonomi kelas atas. Terakhir, makalah ini mengusulkan 'jaringan terfragmentasi biasa' sebagai norma dan menggeser ide-ide sempalan dari hanya bagian kota yang terpinggirkan untuk menggabungkan area dalam 'ruang jaringan premium' sebagai bagian dari urbanisme yang terpecah. Kata kunci. Pusat perkotaan, jaringan terfragmentasi, jaringan jalan, Jakarta.